British America - Bradford, T.G. (Thomas Gamaliel) , 1802-1887 (Cartographer)
Map of Eastern North America, detailing the British territories Upper Canada, Lower Canada, Labrador, Newfoundland, Nova Scotia, New Brunswick, and Prince Edward Island. Showing cities, ports, rivers, and lakes. Originally published : A Comprehensive Atlas, Geographical, Historical & Commercial. By T.G. Bradford. William D. Ticknor, Boston. Wiley & Long, New-York. Scale 1:11,500,000 Relief shown pictorally. Highlights municipal districts in Upper and Lower Canada. Lake Nipissing looks like a crumpled ball of paper. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .